Vulnerabilities shape risk perception and influence adaptive strategies to hydro-meteorological hazards: A case study of Indo-Fijian farming communities. (August 2021) - Anshuka, Anshuka; van Ogtrop, Floris F.; Sanderson, David; Thomas, Erin; Neef, Andreas
Abstract: Unique vulnerabilities are intrinsic to Pacific Island Countries which shape risk perception and influence adaptive decision making to natural hazards. This study aims to examine ongoing risks caused by hydro-meteorological hazards, with a focus on micro-level household response to increasing vulnerabilities, in addition to macro-level community related vulnerabilities. Data collection was undertaken through semi-structured interviews in three hydro-meteorological hazard-prone communities, dominated by members of the Indi-Fijian community, that is, the Indian diaspora, in the Western part of Fiji. The findings were analysed using descriptive, interpretive and inferential analysis. The findings reveal that climatic, physical, cultural and socio-economic factors render households more vulnerable at a micro-level. The research also revealed that members of the Indian community normally have lower levels of societal cohesion, have an inherent individualistic approach to disasters and lack access to communal assets such as land, rendering them more vulnerable at a community level. As a coping mechanism, households were found to have a higher likelihood of adhering to social adaptive strategies such as making behavioural, informational, and educational changes for risk reduction. According to this study, participants show a high degree of risk perception with a sound understanding of storm surge, flood peaks and extents as well as prolonged dry spells. The study recommends avenues for combining scientific knowledge together with citizen science for better hazard risk analysis as future research. To ensure appropriate risk mitigation, governments should implement effective warning systems and undertake capacity building prior to disasters to initiate adequate response to forecast warnings.